PROTECTION OF INTENSIVE APPLE GARDENS FROM SHIELDS (Archive of Conferences, 2021)
There are a number of problems in the world population growth, further increase in the volume of fruit products and the constant supply of quality fruit products, increase productivity, reduce damage caused by pests. Accordingly, protection of the cultivated apple crop from pest damage is a topical issue. Fruits grown in the conditions of our republic have always been distinguished by their taste and high quality. In the cultivation of apples in our country with the use of modern technologies, it is important to test high-yielding, high-quality apple varieties and their introduction into mass production.